Meningkatkan Minat Membeli Produk Nasha Beauty melalui Hadiah Virtual dan Diskon Harga: Peran Mediasi Pembelian Impulsif pada Live Streaming Tiktok - Intansari, Badiiah; Syahputra, Erwin (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
This study aims to analyze the influence of virtual gifts and price discounts on consumer purchase intention of Nasha Beauty products with impulsive buying as a mediating variable in the context of TikTok live streaming. This study uses a quantitative approach with a survey method. Data were collected using a purposive sampling technique from 95 respondents who are generation Z TikTok users and have followed Nasha Beauty's live broadcasts. Data analysis was conducted using SmartPLS 4 software. The results showed that virtual gifts and price discounts have a significant effect on impulse buying and purchase intention. Impulsive buying is proven to mediate the relationship between these two variables with consumer purchase intention. These findings indicate that marketing strategies through interactive features and discount promotions during live streaming are proven effective in attracting consumer attention and purchasing decisions.